Green Synthesis of Fe3O4 Nanoparticles Stabilized by a Garcinia mangostana Fruit Peel Extract for Hyperthermia and Anticancer Activities - Yusefi M (Dove Medical Press, 2021)
Mostafa Yusefi,1 Kamyar Shameli,1 Ong Su Yee,1 Sin-Yeang Teow,2 Ziba Hedayatnasab,3,4 Hossein Jahangirian,5 Thomas J Webster,5 Kamil Kuča1,6 1Department of Chemical and Environmental Engineering, Malaysia-Japan International Institute of Technology, Universiti Teknologi Malaysia, Kuala Lumpur, 54100, Malaysia; 2Department of Medical Sciences, School of Medical and Life Sciences, Sunway University, Petaling Jaya, Selangor Darul Ehsan, 47500, Malaysia; 3Department of Chemical Engineering, Faculty of Engineering, University of Malaya, Kuala Lumpur, 50603, Malaysia; 4Department of Chemical and Petroleum Engineering, Sharif University of Technology, Tehran, 11155-9465, Iran; 5Department of Chemical Engineering, College of Engineering, Northeastern University, Boston, MA, 02115, USA; 6Department of Chemistry, Faculty of Science, University of Hradec Kralove, Hradec Kralove, Czech RepublicCorrespondence: Kamyar Shameli; Kamil Kuča Email kamyarshameli@gmail.com; kamil.kuca@uhk.czIntroduction: Fe3O4 nanoparticles (Fe3O4 NPs) with multiple functionalities are intriguing candidates for various biomedical applications.Materials and Methods: This study introduced a simple and green synthesis of Fe3O4 NPs using a low-cost stabilizer of plant waste extract rich in polyphenols content with a well-known antioxidant property as well as anticancer ability to eliminate colon cancer cells. Herein, Fe3O4 NPs were fabricated via a facile co-precipitation method using the crude extract of Garcinia mangostana fruit peel as a green stabilizer at different weight percentages (1, 2, 5, and 10 wt.%). The samples were analyzed for magnetic hyperthermia and then in vitro cytotoxicity assay was performed.Results: The XRD planes of the samples were corresponding to the standard magnetite Fe3O4 with high crystallinity. From TEM analysis, the green synthesized NPs were spherical with an average size of 13.42± 1.58 nm and displayed diffraction rings of the Fe3O4 phase, which was in good agreement with the obtained XRD results. FESEM images showed that the extract covered the surface of the Fe3O4 NPs well. The magnetization values for the magnetite samples were ranging from 49.80 emu/g to 69.42 emu/g. FTIR analysis verified the functional groups of the extract compounds and their interactions with the NPs. Based on DLS results, the hydrodynamic sizes of the Fe3O4 nanofluids were below 177 nm. Furthermore, the nanofluids indicated the zeta potential values up to − 34.92± 1.26 mV and remained stable during four weeks of storage, showing that the extract favorably improved the colloidal stability of the Fe3O4 NPs. In the hyperthermia experiment, the magnetic nanofluids showed the acceptable specific absorption rate (SAR) values and thermosensitive performances under exposure of various alternating magnetic fields. From results of in vitro cytotoxicity assay, the killing effects of the synthesized samples against HCT116 colon cancer cells were mostly higher compared to those against CCD112 colon normal cells. Remarkably, the Fe3O4 NPs containing 10 wt.% of the extract showed a lower IC50 value (99.80 μg/mL) in HCT116 colon cancer cell line than in CCD112 colon normal cell line (140.80 μg/mL).Discussion: This research, therefore, introduced a new stabilizer of Garcinia mangostana fruit peel extract for the biosynthesis of Fe3O4 NPs with desirable physiochemical properties for potential magnetic hyperthermia and colon cancer treatment.Keywords: green synthesis, Fe3O4 nanoparticles, Garcinia mangostana, magnetic hyperthermia, cytotoxicity assay